PENGARUH KOMPENSASI DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PADA PT KRISTAL KOMPUTERINDO PERKASA - Eni, Eni; Realize (SCIENTIA JOURNAL, 2022)
In an organization, human resources become an important function in increasing competition in a company. This research was conducted to determine whether the effect of compensation and job satisfaction on the performance of employees of PT Kristal Computerindo Perkasa. The type of research used is descriptive quantitative. Then the population in this study were all employees at PT Kristal Computerindo Perkasa, amounting to 110 people. The sampling technique that the researcher uses in this research is to use a saturated sampling technique, where the determination of the sample is taken from all the existing population. In this study, the research collected data using interview, observation, and questionnaire techniques. From the results of the questionnaire then processed using the SPSS version 25 application, by obtaining the results of compensation having a positive and significant effect on employee performance with a significance value of 0.000 <0.05, and job satisfaction having a positive and significant effect on employee performance with a significance value of 0.000 < 0.05 and compensation and job satisfaction have a positive and significant effect on employee performance with a significance value of 0.000 <0.005